Impact of Drug Treatment at Neonatal Ages on Variability of Drug Metabolism and Drug-drug Interactions in Adult Life - Piekos, Stephanie (Curr Pharmacol Rep, 2017)
PURPOSE OF REVIEW: As the number of patients taking more than one medication concurrently continues to increase, predicting and preventing drug-drug interactions (DDIs) is now more important than ever. Administration of one drug can cause changes in the expression and activity of drug metabolizing enzymes (DMEs) and alter the efficacy or toxicity of other medications that are substrates for these enzymes, resulting in a DDI. In today’s medical practice, potential DDIs are evaluated based on the current medications a patient is taking with little regard to drugs the patient has been exposed to in the past. The purpose of this review is to discuss potential impacts of drug treatment at neonatal ages on the variability of drug metabolism and DDIs in adult life. RECENT FINDINGS: Existing evidence from the last thirty years has shown that exposure to certain xenobiotics during neonatal life has the potential to persistently alter DME expression through adult life. With recent advancements in the understanding of epigenetic regulation on gene expression, this phenomenon is resurfacing in the scientific community in hopes of defining possible mechanisms. Exposure to compounds that have the ability to bind nuclear receptors and trigger epigenetic modifications at neonatal and pediatric ages may have long-term, if not permanent, consequences on gene expression and DME activity. SUMMARY: The information summarized in this review should challenge the way current healthcare providers assess DDI potential and may offer an explanation to the significant interindividual variability in drug metabolism that is observed among patients.